Psychoneuroimmunological Relationships in Women With Fibromyalgia. (April 2013) - Menzies, Victoria; Lyon, Debra E.; Elswick, R. K.; Montpetit, Alison J.; McCain, Nancy L.
Introduction: The purpose of this pilot study was to characterize the relationships among perceived stress, pain, fatigue, depression, anxiety, biomarkers, and functional status in women with fibromyalgia syndrome (FMS) using a psychoneuroimmunological (PNI) framework. Materials and Method: Using a cross-sectional, correlational design, the authors asked 50 women diagnosed with FMS to complete the Perceived Stress Scale (PSS), Brief Pain Inventory (BPI), Brief Fatigue Inventory (BFI), Center for Epidemiological Studies—Depression scale, State–Trait Anxiety Inventory (STAI), and Functional Impact Questionnaire. The authors analyzed plasma levels of 17 cytokines using a BioPlex® assay and levels of C-reactive protein (CRP) using a high-sensitivity enzyme-linked immunosorbent assay (ELISA). Results: Compared to published guidelines (>3 mg/L reflects high inflammation), CRP levels were elevated in participating women. Perceived stress demonstrated positive correlations with pain, fatigue, depression, anxiety, and functional status and negative correlations with monocyte chemotactic protein (MCP)-1( r = −.30) and interleukin-1 beta (IL-1β; r = −.29). Pain severity correlated with macrophage inflammatory protein (MIP)-1β ( r = .29), and pain interference negatively correlated with IL-1β ( r = −.30). Fatigue negatively correlated with IL-1β ( r = −.32), interleukin-10 (IL-10; r = −.31), and granulocyte colony-stimulating factor (G-CSF; r = −.31). Depressive symptoms correlated with CRP ( r = .31). Discussion: Relationships among perceived stress and symptoms supported the PNI framework. Study findings are similar to previous studies showing that cytokines in persons with FMS do not show a consistent pattern. The elevated CRP levels suggest higher levels of generalized inflammation in the sample and provide evidence for continued development of biobehavioral interventions to address both symptoms and their biological markers over time.